Causes and management of drug-induced long QT syndrome - Ayad, Ramy F. (Baylor Health Care System, 2010)
Long QT syndrome (LQTS) is characterized by inherited or acquired prolonged QT interval on the surface electrocardiogram. This can lead to torsade de pointes ventricular tachycardia (TdP VT) and ventricular fibrillation. In the acquired form of the disease, medications from several classes can cause TdP VT or potentiate the electrocardiographic findings. These include class IA and III antiarrhythmics, antibiotics (macrolides and quinolones), antidepressants (tricyclics and selective serotonin reuptake inhibitors), antipsychotics (haloperidol and phenothiazines), and antiemetics (ondansetron and prochlorperazine). We present four cases of drug-induced LQTS resulting in life-threatening cardiac arrhythmias. Antiarrhythmic medications were the cause in two cases, and the other two cases involved noncardiac medications. All four patients had at least one risk factor for LQTS in addition to the offending drug, including female gender, hypokalemia, hypomagnesemia, and bradycardia. In one patient, amiodarone was administered for treatment of VT, although the correct diagnosis was actually TdP VT. In patients with polymorphic VT or ventricular fibrillation without a significant history of cardiovascular disease, drug-induced LQTS should be high in the differential diagnosis. Prompt diagnosis is key, as amiodarone, while often used to suppress VT, is potentially harmful in the setting of LQTS and TdP VT.